Preparasi Minyak Goreng Bekas sebagai Bahan Baku Pembuatan Biodiesel dengan Adsorben Arang Aktif dari Tempurung Kelapa - Haryono (ReTII, 2025)
Cooking oil, particularly from palm oil, is a primary need in households and the food and culinary industry. The use of this cooking oil ultimately results in waste in the form of waste cooking oil. Waste cooking oil has the potential to be used as a raw material in the production of biodiesel, a type of renewable energy. However, before being used in the biodiesel production process, the waste cooking oil must be separated from its impurities. One method in the impurity separation stage from waste cooking oil is adsorption with various types of adsorbents, such as activated charcoal. Coconut shells are a potential biomass waste as a raw material for producing activated charcoal. The aim of this study was to determine the effect of temperature and adsorbent content on the adsorption of waste cooking oil with activated charcoal from coconut shells on the characteristics of waste cooking oil as a raw material for biodiesel synthesis. The research procedure includes two main stages, namely the purification of waste cooking oil by sedimentation, filtration, evaporation, and sedimentation methods; then the synthesis of biodiesel from waste cooking oil after purification. The results of the study showed that the adsorption of waste cooking oil at a temperature of 70 °C and an activated charcoal content as an adsorbent of 5% (w/v) produced waste cooking oil with the best quality, based on the parameters of density, viscosity, acid number, and iodine number. Biodiesel produced from waste cooking oil that has been purified under optimal adsorption conditions has met the biodiesel quality standards according to Indonesian National Standard, SNI 7182-2015.